Mild cognitive impairment among elderly persons residing in an urban resettlement colony in Delhi - M G Thejas Achary; Ravneet Kaur; Deepti Vibha; Kalaivani Mani; Shashi Kant; Sanjeev Kumar Gupta (Wolters Kluwer Medknow Publications, 2023)
Background: Mild cognitive impairment (MCI) is a transitional state between normal cognition and clinical dementia. MCI is associated with an increased risk of dementia and mortality. Progression of MCI to dementia can be prevented by cognitive and lifestyle interventions. There is limited evidence on the burden and risk factors associated with MCI in India. To estimate the prevalence of MCI among elderly persons, and to study the factors associated with MCI. Materials and Methods: This community-based cross-sectional study was carried out among 365 persons aged 60 years or older, residing in an urban resettlement colony of Delhi. Participants with dementia (score <23 on the Hindi version of the Mini-Mental State Examination) were excluded. Objective cognitive impairment and functional disability were assessed by the Montreal Cognitive Impairment-Basic (MoCA-B) tool and Barthel's Activities of Daily Living, respectively. The prevalence of MCI was estimated by Petersen's criteria, i.e., subjective memory impairment, objective cognitive impairment (MoCA score 19-25), functional independence, and absence of dementia. Univariate analysis was performed, followed by stepwise multivariate logistic regression. The association of socio-demographic and other health conditions with MCI was assessed. Results: The prevalence of MCI was 9.3% [95% confidence interval (CI) 6.7-12.7], 13.3% (95% CI 8.8-19.7) among men, and 6.5% (95% CI 3.9-10.6) among women. The risk of MCI was higher among current smokers. Conclusions: MCI was common among the elderly. Early detection of MCI may be included in health programs for elderly persons.